Strategi Pemasaran Digital untuk Meningkatkan Pendapatan di Institusi Pendidikan di Era Digital - Ardin Sianipar; Widya Angelia; Natalina Damayanthi (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2026)
This study aims to identify digital marketing strategies that enhance revenue streams in educational institutions, with a focus on developing countries such as Indonesia and on advanced technologies like AI and VR. A Systematic Literature Review (SLR) following PRISMA guidelines analyzed 25 peer-reviewed articles from 2020 to 2025, sourced from Scopus, Web of Science, and Google Scholar. Keywords included "digital marketing" and "revenue stream." Thematic analysis evaluated strategies, impacts, and influencing factors. SEO, social media, and AI-driven personalization increased enrollment by 25%, enhanced visibility by 200% compared with traditional methods, and improved ROI by 200%. Donations increased by 18%, and revenue from the adult segment rose by 42%, despite a 15–20% decline in post-pandemic enrollment. Technology infrastructure and collaboration support success, while skill gaps and privacy regulations hinder progress. This research uniquely focuses on the revenue impact of digital marketing in education, particularly in low-adoption regions such as Indonesia. It integrates AI, VR, and Generation Z behavior, addressing gaps in data ethics and multichannel strategies. Institutions should prioritize SEO, social media, and staff training, while adopting and implementing effective privacy policies. Influencer collaborations and CRM investments can enhance engagement and revenue. Governments should support digital training and implement balanced regulation to foster sustainable growth.